Mapping paleocoastlines and continental flooding during the Phanerozoic - Kocsis, Ádám; Scotese, Christopher R. (Earth-Science Reviews, 2021)
Sea levels shape the face of the Earth, define processes of sedimentation, and influence the evolution of life via the distribution of habitats. Ancient topographies can be reconstructed using the history and understanding of tectonic processes, lithological evidence, and present-day topographies. Paleogeographic reconstructions must accommodate ever newer sources of geological data, so we can refine and improve our model of ancient topography and bathymetry. Here, we assess the accuracy of a set of Phanerozoic digital paleogeographic maps by testing the proposed distribution of flooded shallow seas and land using fossil occurrence data from the Paleobiology Database. After noting a moderate match, we modified the positions of the coastlines and continental margins of these topographic models to reflect times of maximum transgression. Using the updated paleogeographic maps, we outline the changes of land and shallow marine areas over time and suggest ways they can be used for further investigations of our planet's history.
CRIS-Team Scopus Importer:2021-01-08
Keywords: Coastlines; Continental flooding; Fossils; Global; Paleogeography; Phanerozoic; Reconstruction